The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/ijms18092018
|View full text |Cite
|
Sign up to set email alerts
|

Rhein Induces Oxidative Stress and Apoptosis in Mouse Blastocysts and Has Immunotoxic Effects during Embryonic Development

Abstract: Rhein, a glucoside chemical compound found in a traditional Chinese medicine derived from the roots of rhubarb, induces cell apoptosis and is considered to have high potential as an antitumor drug. Several previous studies showed that rhein can inhibit cell proliferation and trigger mitochondria-related or endoplasmic reticulum (ER) stress-dependent apoptotic processes. However, the side effects of rhein on pre- and post-implantation embryonic development remain unclear. Here, we show that rhein has cytotoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
(72 reference statements)
1
9
0
Order By: Relevance
“…Moreover, mRNA levels of CXCL‐C1C , IL‐1β, and IL‐8 related to innate immunity were downregulated after pretilachlor exposure . Importantly, a recent study by our group showed that rhein, a glucoside chemical component of a traditional Chinese medicine derived from the root of rhubarb, induces apoptosis through ROS generation and downregulation of transcriptional levels of the innate immunity‐related genes, CXCL1 , IL‐1 β, and IL‐8 , in fetuses of dams receiving intravenous injections in an animal model . These results collectively indicate that pretilachlor and rhein have the potential to cause embryonic cytotoxicity and induce oxidative stress and immunotoxicity during zebrafish or mouse embryo development.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, mRNA levels of CXCL‐C1C , IL‐1β, and IL‐8 related to innate immunity were downregulated after pretilachlor exposure . Importantly, a recent study by our group showed that rhein, a glucoside chemical component of a traditional Chinese medicine derived from the root of rhubarb, induces apoptosis through ROS generation and downregulation of transcriptional levels of the innate immunity‐related genes, CXCL1 , IL‐1 β, and IL‐8 , in fetuses of dams receiving intravenous injections in an animal model . These results collectively indicate that pretilachlor and rhein have the potential to cause embryonic cytotoxicity and induce oxidative stress and immunotoxicity during zebrafish or mouse embryo development.…”
Section: Discussionsupporting
confidence: 54%
“…Rhein is found in R. palmatum L., Aloe barbadensis Miller, Cassia angustifolia Vahl and P. multiflorum Thunb, [ 77 ] which has anti‐inflammatory, [ 78 ] anti‐cancer, [ 79 ] antioxidant [ 80 ] and neuroprotection activities. [ 81 ] Rhein could improve recognition memory impairment, alleviate neuroinflammation and BDNF deficits in the perirhinal cortex on high‐fat‐diet‐induced animal model.…”
Section: Quinones and Its Role In Admentioning
confidence: 99%
“…Previous reports and our studies demonstrated that decrease in the cell numbers of TE and/or ICM lineages induces disruption of embryo implantation and fetus viability, leading to miscarriage. 28,33,34,[39][40][41][42] Here, GRb1 treatment during oocyte maturation triggered either an increase or decrease in ICM, TE and total cell numbers at the blastocyst stage, dependent on the dosage (Figure 2A).…”
Section: Discussionmentioning
confidence: 96%